Effect Of Fermented Cassava Peel (Manihot utilisima) On Performances Of Male Sheep - Masrayani Pulungan; Iskandar Sembiring; Ma`ruf Tafsin; Hamdan .; Nevy Diana Hanafi (Universitas Sumatera Utara, 2017)
Abstract.The experiment aimed to find effect of cassava peel (manihot utilisima) which fermented on performance of local sheep male. The research was conducted at Jl. Bunga Rinte, Simpang Selayang, Medan, in October - December 2017 using Completely Randomized Design (CRD) with 4 treatments and 5 replications. The experiment used 20 of local sheep male weaning with initial body weight of 10.18 ± 1kg. The treatment provided is P0 (Fermented Cassava peel 0%), P1 (Fermented Cassava peel 20%), P2 (Fermented Cassava peel 40%), and P3 (Fermented Cassava peel 60%). The observed of parameters are feed comsumption, average daily gain, feed vonversion (FCR) and income over feed cost (IOFC). The result of this research indicated that utilization of cassava peel (Manihot utiliima)fermented on performance of local sheep with the average consumption of sheep feed (g/head/day) are: 330.01; 364.99; 391.76; and 402.92, average daily gain (g/head/day): 52.86; 71.88; 84.36; and 101.80 and ration conversion: 6.42; 5.17; 4.78; dan 4.04. The conclusion of this research is the higher use of fermented cassava peel the better also the effect on improve of body weight, feed consumption and conversion of local males feed. The highest IOFC value is found in P3 with an average of Rp.276.656,01 during the research.